Crystal macropatterns in leaves of Fagaceae and Nothofagaceae: a comparative study - Lersten, N. R.; Horner, Harry T. (Plant Systematics and Evolution, 2008)
Crystal macropatterns in Fagaceae and Nothofagaceae were examined from cleared herbarium leaves (eight genera, 122 spp.) by polarizing microscopy. Prisms and druses dominate, but previously undescribed intermediate forms occur in 25 species of Fagaceae. Sixty-two species had only prisms associated with vein orders 1–4, but smallest orders 5 and 6 had few or no crystals. In mesophyll, 98 species had small druses in spongy parenchyma and larger but fewer druses in palisade parenchyma. Subfamily Fagoideae conformed closely to this macropattern, Castaneoideae less so. Six Castaneoideae species lacked vein crystals. Two Fagoideae species and seven Nothofagus species lacked mesophyll crystals. Druses with prominent cores occur throughout Fagaceae but none were seen in Nothofagaceae. Tabular presentation of results shows signiﬁcant although overlapping trends from Fagoideae to Castaneoideae to Nothofagaceae, with the latter taxon deviating most from Fagaceae.
Keywords: Calcium oxalate; crystals; Fagaceae; leaf anatomy; macropatterns; Nothofagaceae